Analysis of Student Management Strategies in Strengthening Extracurricular Achievements in Scouting at SMAN 1 Cisaga Ciamis - R. Supyan Sauri; Wawan Kuswanda; Rini Riyanti; Leni Eka Yuniar; Nenden Rosmaya (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to analyze student management strategies in supporting extracurricular Scout activities and their impact on character building and student achievement at SMAN 1 Cisaga, Ciamis. The background of this study is based on the reality of the low effectiveness of scout activities in schools, which results in minimal student involvement and suboptimal character-building outcomes. This study employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation and analyzed using Miles and Huberman’s interactive model. The results indicate that the main challenges in implementing scouting activities include low student participation, limited resources, low motivation, insufficient trainer training, and poor communication. The student management strategies implemented include the development of participatory programs, capacity building for instructors, and creating a supportive environment. Systematic scouting activities have been shown to improve discipline, leadership, independence, and academic achievement among students. This study recommends strengthening participatory and evaluative extracurricular management policies and cross-sector collaborations to support successful character building through scouting. These findings are expected to contribute to more responsive and contextual educational management practices at the secondary-school level. Keywords: Student Management, Scouting, Extracurricular Abstrak. Penelitian ini bertujuan untuk menganalisis strategi manajemen kesiswaan dalam mendukung kegiatan ekstrakurikuler Pramuka dan dampaknya terhadap pembentukan karakter serta prestasi siswa di SMAN 1 Cisaga, Ciamis. Latar belakang penelitian didasarkan pada realitas rendahnya efektivitas pelaksanaan Pramuka di sekolah, yang berakibat pada minimnya keterlibatan siswa dan tidak optimalnya hasil pembinaan karakter. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa tantangan utama dalam pelaksanaan kegiatan Pramuka meliputi partisipasi siswa yang rendah, keterbatasan sumber daya, rendahnya motivasi, kurangnya pelatihan pembina, dan lemahnya komunikasi. Strategi manajemen kesiswaan yang diterapkan meliputi penyusunan program partisipatif, pengembangan kapasitas pembina, dan penciptaan lingkungan pendukung. Kegiatan Pramuka yang dikelola secara sistematis terbukti mampu meningkatkan kedisiplinan, kepemimpinan, kemandirian, serta prestasi akademik siswa. Penelitian ini merekomendasikan penguatan kebijakan manajemen ekstrakurikuler berbasis partisipatif dan evaluatif, serta kolaborasi lintas pihak untuk mendukung keberhasilan pembinaan karakter melalui Pramuka. Temuan ini diharapkan berkontribusi terhadap praktik manajemen pendidikan yang lebih responsif dan kontekstual di tingkat sekolah menengah. Kata kunci: Manajemen Kesiswaan, Pramuka, Ekstrakurikuler